A protocol for nitrogen isotopic measurement of dissolved organic nitrogen with a combination of oxidation-denitrification and gas phase diffusion methods. Issue 6 (2nd November 2021) - Cao, Hai Thi Thuy; Nakamura, Takashi; Toyama, Tadashi; Nishida, Kei
ABSTRACT: Isotopic tracing technique is one of the most effective methods to identify nitrogen source and fate in aquatic environments. Although dissolved organic nitrogen (DON) is a key component in nitrogen cycles, information on nitrogen stable isotope ratios in DON ( δ 15 N-DON) is limitedly available for its low recovery through a direct measurement. Indirect measurement is based on mass balance calculations and easy to use with high recovery of DON. However, in theory, the result from mass balance calculation is sensitive to the level of DON content, and its applicability remains to be examined for waters containing a variety of DON content in total dissolved nitrogen (TDN). In this study, we established a protocol for indirect measurement of δ 15 N-DON values based on the combination of multiple analytical methods. Precision and accuracy in the measurement were assessed by varying the composition of DON and dissolved inorganic nitrogen, and quantitation thresholds were presented at different acceptable levels. The results illustrated an advantage of the developed protocol possibly applicable to water samples particularly with low DON content that is commonly detected in freshwater. This method is expected to expand the use of isotope tracing techniques for understanding the nitrogen cycle in water environments.